Effects of curing conditions on crack bridging response of PVA reinforced cementitious matrix - Esmaeeli, Esmaeel (2012)
The effect of the different curing conditions on the response of fiber crack bridging of PVAECC is studied. The self compacting PVA-ECC was cast into the moulds to produce four similar rectangular panels. These panels were kept under different curing conditions for 28 days. The tensile specimens were cut from these panels, and after executing a notch they were tested under tensile loading. The stress versus crack opening relationship for the specimens extracted from panels cured at different conditions is obtained, and the derived results are compared. The dispersion of results, the stress at crack initiation, the maximum fibers bridging stress and the corresponding crack opening, the absorbed energy and the fibers bridging stiffness are the investigated parameters. Also macroscopic images of the fibers in fracture surface are used to interpret the obtained data. As a result of this study a significant influence of different curing conditions on the fiber crack bridging response was observed.